EFFECT OF ACTIVITY-BASED TEACHING-LEARNING STRATEGY ON STUDENTS’ ACHIEVEMENT IN MATHEMATICS - SHARMA, BRAJESH KUMAR; NARAYANA, U. L.; SUBRAMANIAM, K. B. (THE PRIMARY TEACHER, 2013)
Pupils tend to learn mathematics through a meaningful approach to mathematics rather than by mechanical process. Therefore, for teachers as well as students of mathematics subject, learning methods are very important. Method is nothing but a scientific way of presenting the subject, keeping in mind the psychological and physical requirements of the children. For effective learning of mathematics the method has to be as good as the content. There are various methods used in mathematics teaching-learning. But, activity-based teaching-learning strategy is very useful in mathematics teaching-learning. Therefore, in this paper, the researchers had made an attempt to study the effect of activity-based teaching learning strategy on students’ achievement in mathematics.